2017
DOI: 10.1017/s0022226717000305
|View full text |Cite
|
Sign up to set email alerts
|

Rhythmic stress in Ukrainian: Acoustic evidence of a bidirectional system

Abstract: Bidirectional stress systems with internal lapses are rare and their existence has been recently called into question (Newlin-Łukowicz 2012). The present paper reports an acoustic study of secondary stress in Ukrainian based on polysyllabic words with lexical stress located at or near the right edge of the word. The results indicate that Ukrainian has an iteration of secondary stresses from the left edge towards the lexical stress, rather than in the opposite direction. This characteristic makes it metrically … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(21 citation statements)
references
References 26 publications
1
19
1
Order By: Relevance
“…Previous research has demonstrated that increased duration cues rhythmic stress in Ukrainian ( [10], [11], [14]). However, these studies concentrated on duration, intensity and pitch and did not investigate vowel quality as a potential variable contributing to the expression of rhythmic prominence.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Previous research has demonstrated that increased duration cues rhythmic stress in Ukrainian ( [10], [11], [14]). However, these studies concentrated on duration, intensity and pitch and did not investigate vowel quality as a potential variable contributing to the expression of rhythmic prominence.…”
Section: Discussionmentioning
confidence: 99%
“…[8], [9]). The current study investigates vowel undershoot in Ukrainian, a language exhibiting several degrees of lengthening within one word ( [10], [11], [12]). These durational differences render Ukrainian a perfect testing ground for the theories of phonetic reduction as a durationdependent undershoot.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations